Sustainable solid soap production using recycled cooking oil with ecoenzyme and lemongrass extract - Zona Octarya; Elvi Yenti; Lisa Utami; Yusbarina (Acta Biochimica Indonesiana)
Background: Improper disposal of used cooking oil poses significant environmental challenges, including groundwater contamination and harm to aquatic ecosystems. Recycling used cooking oil into solid soap offers a sustainable solution to reduce waste while creating a valuable, eco-friendly product.